Loss of MEG3 and upregulation of miR-145 play an important role in the invasion and migration of Cr(VI)-transformed cells. Issue 8 (August 2022) - Zhang, Zhuo; Li, Jingxia; Yan, Bo; Tu, Huailu; Huang, Chao; Costa, Max
Abstract: Chronic exposure of human bronchial epithelial BEAS-2B cells to hexavalent chromium (Cr(VI)) causes malignant cell transformation. These transformed cells exhibit increases in migration and invasion. Neuronal precursor of developmentally downregulated protein 9 (NEDD9) is upregulated in Cr(VI)-transformed cells compared to that of passage-matched normal BEAS-2B cells. Knockdown of NEDD9 by its shRNA reduced invasion and migration of Cr(VI)-transformed cells. Maternally expressed gene 3 (MEG3), a long noncoding RNA, was lost and microRNA 145 (miR-145) was upregulated in Cr(VI)-transformed cells. MEG3 was bound to miR-145 and this binding reduced its activity. Overexpression of MEG3 or inhibition of miR-145 decreased invasion and migration of Cr(VI)-transformed cells. Overexpression of MEG3 was able to decrease miR-145 level and NEDD9 protein level in Cr(VI)-transformed cells. Ectopic expression of MEG3 was also shown to reduce β-catenin activation. Inhibition of miR-145 in Cr(VI)-transformed cells decreased Slug, an important transcription factor that regulates epithelial-to-mesenchymal transition (EMT). Inhibition of miR-145 was found to increase MEG3 in Cr(VI)-transformed cells. Further studies showed that mutation of MEG3 at the binding site for miR-145 did not change NEDD9 and failed to decrease invasion and migration. The present study demonstrated that loss of MEG3 and upregulation of miR-145 elevated NEDD9, resulting in activation of β-catenin and further upregulation of EMT, leading to increased invasion and migration of Cr(VI)-transformed cells. Abstract : Cr(VI); MEG3; miR-145; NEDD9; Invasion; Migration.